2018
DOI: 10.7748/nm.2018.e1684
|View full text |Cite
|
Sign up to set email alerts
|

Reflective practices: meaningful recognition for healthy work environments

Abstract: Nurses' decisions about their intent to remain in the workforce are based on various factors. A healthy work environment in which work done well is recognised and appreciated contributes to nurses' satisfaction and better patient outcomes. This article examines the American Association of Critical-Care Nurses framework for a healthy work environment, focusing on standards for meaningful recognition. Reflective practice, which provides a self-analytical approach to appreciate and value one's work, is viewed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Health care leaders must contribute to reflective practices and work environments so nurses can create space for discussing their emotional labor. Sherwood et al (2018) argue that reflective practices for nurses provide ways to enhance self-esteem by sharing experiences at work. Through reflective practices for nurses, the emotional labor of caring for ill parents and their children can become increasingly acknowledged, visible, and manageable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health care leaders must contribute to reflective practices and work environments so nurses can create space for discussing their emotional labor. Sherwood et al (2018) argue that reflective practices for nurses provide ways to enhance self-esteem by sharing experiences at work. Through reflective practices for nurses, the emotional labor of caring for ill parents and their children can become increasingly acknowledged, visible, and manageable.…”
Section: Discussionmentioning
confidence: 99%
“…Building emotional intelligence among individual nurses is regarded as essential to strengthen emotional competence (Smith et al, 2009), which should be developed and refined at the workplace through collegial support and in nursing education through lectures, skills training, and clinical supervision. Collegial support could be promoted by advancing a learning culture and reflective practices in health care organizations (Sherwood et al, 2018). Reflective practices for nurses provide ways to enhance self-esteem by sharing their experiences in unit meetings and group discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical findings are generated from data collected in rural communities of this area between 2015 and 2018 during the implementation of the MOSMAC project. Since the MOSMAC project was implemented by the first author through a grant from USAID, this study emerges as part of self-reflection on development practice (Sherwood et al, 2019). 5 Data were collected using qualitative ethnographic methods including focus group discussions (n=9), continuous participant observation, key informant interviews (n=8), official meetings and community workshops (n=2).…”
Section: Study Context and Methodsmentioning
confidence: 99%
“…23 Although there is much research on the abilities of individual nurses in regard to EBP, the importance of the context in which interventions are to occur cannot be overstated. 23,[26][27][28] Nurse-led research and EBP projects have demonstrated benefits in clinical settings, [29][30][31] yet only an estimated 25% of clinical decisions are made based on evidence, and an even lower percentage results in major changes within the nursing profession. [32][33][34][35] These low implementation rates indicate that the challenges in translating research findings and evidence into practice include issues beyond those of individual knowledge and skill development.…”
Section: Implementing Evidence Informed Practice Changesmentioning
confidence: 99%